Implementasi Kebudayaan Melayu dalam Pelajaran Sejarah - Suroyo Suroyo; Bima Putra; Bedriati Ibrahim; Yanuar Yanuar; Asyrul Fikri; Bunari Bunari (Salus Cultura: Jurnal Pembangunan Manusia dan Kebudayaan, 2021)
History subject, as one of the topics with the capacity to mold the nation's character, should stress mentality or emotional intelligence as well as knowledge or academic intelligence. This study employs the Library Research approach, which entails gathering information and data from existing book sources such as Malay history and culture books, past journals, and historical knowledge books. This is part of the Malay culture's character, and character building in the Malay community may be used in any learning topic, particularly history subject. The goal of this study is to demonstrate how Riau Malay culture is being included into history classes. The problem in the area is that the Malay character is not accommodated in school learning; it is doubtful that this generation in Riau Province would conduct in accordance with the Malay personality. Otherwise, Malay culture is implemented or used in every subject, particularly history instruction. However, implementation Malay culture of Riau into history education may be an input and source of information where instructors can apply character development to pupils while also developing historical education understanding.